2011
DOI: 10.1002/lapl.201110048
|View full text |Cite
|
Sign up to set email alerts
|

Optical image analysis of fat cells for indocyanine green mediated near-infrared laser treatment

Abstract: Fat tissue engineering by near-infrared laser treatment is investigated in vitro. For the quantitative estimation of efficiency of treatment and consequential processes on the cellular level, a computational method for optical image analysis is proposed. The method is based on the fractal dimension data analysis of fat cell structure. The conducted experiments confirm the feasibility of the proposed method to obtain quantitative information of the cellular processes. The results indicate that the proposed meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Photodynamic therapy (PDT) has emerged as a promising therapeutic modality for the treatment of oncological diseases [1,2]. It has the advantage of dual selectivity, due to the preferential localization of the photosensitizer by the malignant tissue and restriction of photoactivation to the tumor site due to localized light irradiation [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy (PDT) has emerged as a promising therapeutic modality for the treatment of oncological diseases [1,2]. It has the advantage of dual selectivity, due to the preferential localization of the photosensitizer by the malignant tissue and restriction of photoactivation to the tumor site due to localized light irradiation [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Manipulat ing light flounce rate, timing of illumination following photosensitizer administration or a combination of these it is possible to modulate the role played by each of these factors in the final damage towards the tumor. Studies from in vitro culture systems and in vivo ani mal models have indicated that both necrosis and apo 1 The article is published in the original. ptosis of the target cells or tissues represent the major therapeutic effect of PDT [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides experiences from new laser systems for practi cal use [29], recent imaging techniques [30,31] can improve future investigations of the dosimetry of light in ophthalmology. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these terms reflects the specificity of biochemical and morphological approaches . Depending on technology applied, cell apoptosis or necrosis may take place . Another method of fat tissue destruction, namely photodynamic/photothermal method, may provide reduction of regional or site‐specific accumulations of adipose tissue least‐invasively .…”
Section: Introductionmentioning
confidence: 99%